2021
DOI: 10.15421/192108
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Orientation and Competitor Awareness on Firm Performance in the Bottled Water Industry

Abstract: Purpose:  To assess the Influence of strategic positioning indicators namely customer orientation and competitor awareness on firm performance in the bottled water Industry, with sector standards as a moderating variable. Design/Method/Approach: This study adopted a quantitative methodology and cross-sectional explanatory study design of which a sample of 424 licensed bottled water firms were randomly selected. Structured questionnaires were distributed to the managers and a factor analysis was used to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The three subthemes extracted were sourcing, Internal processes & procedures and revenue. Lastly, the dependent variable firm performance was construed using twenty (20) indicators measured in a 5-point Likert scale (Ichoroh, 2021), of which the measurement values ranged from strongly agree coded as (5), agree coded (4), neutral (3), disagree ( 2) and ( 1) denoting strongly disagree. The reported reliability for these twenty items was Cronbach alpha 0.864 which exceeded the threshold value Cronbach alpha of 0.7 (Keith, 2018).…”
Section: Results From Factor Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The three subthemes extracted were sourcing, Internal processes & procedures and revenue. Lastly, the dependent variable firm performance was construed using twenty (20) indicators measured in a 5-point Likert scale (Ichoroh, 2021), of which the measurement values ranged from strongly agree coded as (5), agree coded (4), neutral (3), disagree ( 2) and ( 1) denoting strongly disagree. The reported reliability for these twenty items was Cronbach alpha 0.864 which exceeded the threshold value Cronbach alpha of 0.7 (Keith, 2018).…”
Section: Results From Factor Analysismentioning
confidence: 99%
“…The first null hypothesis in this study was that there exists no association between core competencies and firm performance in the bottled water industry. To examine this hypothesis a structural model relating core competencies and performance of firms in the bottled water industry was fitted (Ichoroh, 2021) as is illustrated in Figure 1. The ten items used to measure core competencies were: competence based recruitment of staff (COP2), competitive remuneration (COP3), staff incentives (COP4), employees performance management (COP4b), incentives pegged on performance (COP5), staff engagement in the implementation process (COP6), employees adaptation to changes in plans (COP7), firm's help to employees to shift and pivot in response changes (COP8), firm's changes to employees management (COP9) and firm's shares with employees opportunities available for personal development (COP10).…”
Section: Measurement and Structural Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, proactive market orientation has been found to have an indirect effect on export yields. Another case of Ichoroh, (2021) in his research found that there is a positive and significant relationship between consumer orientation and competitor awareness about company performance. Thus, it is hypothesized: H3: There is a positive relationship between Consumer Orientation (CO) and Innovation Capabilities (IC).…”
Section: Customer Orientationmentioning
confidence: 96%